THE EFFECT OF WORK COMPLIANCE, COMPETENCE AND PERFORMANCE ALLOWANCES ON EMPLOYEE PERFORMANCE AT THE PROVINCIAL PUBLIC WORKS OFFICE OF BINA MARGA AND SPATIAL PLANNING - Mohamad Deni Alpra; Hasmawaty AR (SEAN Institute, 2023)
This study aims to investigate the effect of work compliance, competence, and performance allowances on employee performance at the Provincial Public Works Office of Bina Marga and Spatial Planning. The research method used is a survey with data collection through questionnaires and regression analysis. The results of the analysis show that work compliance, competence, and performance benefits have a significant influence on performance. Employees who show obedience to organizational rules, have good competence, and receive rewards for superior performance, tend to achieve higher performance. The implication of this study is that organizations need to pay attention to and improve these aspects in their human resource management to support the achievement of optimal performance. While this study makes an important contribution, attention to limitations, including the specific context and additional factors that may influence performance, is required. This research can be used as a foundation to guide more effective human resource management policies and practices in various organizations.